Developing video-based learning media for Shielded Metal Arc Welding: A 4D model approach - Imron Fahrudin; Suharno Suharno (Jurnal Pendidikan Vokasi, 2025)
Video-based learning media has the potential to support students’ conceptual understanding in vocational welding courses; however, many available videos focus mainly on procedures and provide limited pedagogical guidance that has been validated by experts. This study aims to develop and evaluate video-based learning media on the topic of the strong influence of welding current in Shielded Metal Arc Welding (SMAW). The study adopted a Research and Development design using the 4D model (Define, Design, Develop, Disseminate). The product was validated by material and media experts and was then implemented with 40 students enrolled in the Welding Technology course in the Mechanical Engineering Education Study Program. Data were collected through documentation, interviews, observations, and questionnaires, and were analyzed using descriptive statistics. The results show that the developed media meets the feasibility criteria. Material experts rated the learning, language, and content aspects at 92% (very good), while media experts rated the display, audio, and presentation aspects at 91% (very good). Student responses reached 89% (very good), indicating that the videos were perceived as attractive, clear, and practical for learning. Overall, the media supports students’ understanding of how variations in welding current affect weld quality and performance. The findings suggest that systematically designed and validated instructional videos can complement classroom and laboratory activities, reduce instructional time, and help students prepare more effectively for practice.